Asymmetric electromagnetic shielding composite film and preparation method and application thereof

By growing MoS2 flower-like shell structures on polypyrrole nanotubes and combining them with non-solvent-induced phase separation technology, an asymmetric electromagnetic shielding composite film was prepared. This solved the problems of high density and secondary pollution of traditional electromagnetic shielding materials, achieving efficient electromagnetic wave absorption and hydrophobic properties, and meeting commercial standards.

CN121045606APending Publication Date: 2025-12-02GUIZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511314044.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-15
Publication Date
2025-12-02

AI Technical Summary

Technical Problem

Traditional electromagnetic shielding materials suffer from high density, complex manufacturing processes, and a tendency to cause secondary pollution. Meanwhile, there is room for improvement in the electromagnetic wave absorption and shielding performance of existing conductive polymer composite materials.

Method used

By growing a flower-like shell structure of MoS2 on polypyrrole nanotubes to form PNTs@MoS2 core-shell nanowires, and combining it with non-solvent-induced phase separation technology, an asymmetric electromagnetic shielding composite film with a three-layer structure was prepared. The conductive filler layer serves as a highly conductive layer, PNTs@MoS2 serves as an impedance matching absorption layer, and the upper layer is a pure polylactic acid matrix layer. This constructs an asymmetric conductive network to improve the absorption-type electromagnetic shielding performance.

Benefits of technology

It significantly improves the absorption performance of electromagnetic waves, reduces secondary radiation problems, and provides effective electromagnetic interference shielding in humid environments. The material surface has excellent hydrophobic properties, and the electromagnetic shielding effectiveness reaches 64.2dB with an absorption coefficient of 0.65, meeting commercial standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121045606A_ABST
    Figure CN121045606A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of hydrophobic electromagnetic shielding materials, and particularly relates to an asymmetric electromagnetic shielding composite film and a preparation method and application thereof. The PNTs are polypyrrole nanotubes, after Na2MoO4. 2H2O and CH4N2S are added and subjected to a high-temperature reaction, a MoS2 flower-shaped shell structure can grow on the PNTs, the layered structure and the high specific surface area of MoS2 contribute to enhancing scattering and absorption of electromagnetic waves, and rich defect sites can induce dielectric polarization to achieve dielectric loss. Introducing the PNTs (at) MoS2 core-shell nanowire as an electromagnetic wave absorbent into a polylactic acid / dichloromethane system, then putting the system into a culture container in which a conductive filler is pre-paved, and standing and volatilizing at room temperature by adopting an ethanol solution as a volatile agent to finally obtain a three-layer asymmetric electromagnetic shielding composite film comprising the conductive filler, the PNTs (at) MoS2 structure and a polylactic acid matrix from bottom to top. And an asymmetric conductive gradient network is constructed, and the EMI shielding performance which mainly focuses on absorption is remarkably improved, so that the secondary radiation problem of electromagnetic waves is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of hydrophobic electromagnetic shielding materials, specifically relating to an asymmetric electromagnetic shielding composite film, its preparation method, and its application. Background Technology

[0002] In recent years, with the rapid development of information technology, the popularity of wearable devices and portable electronic products in contemporary society has increased significantly. This trend has not only changed people's lifestyles but also sparked widespread concern about electromagnetic radiation pollution. The aggravation of electromagnetic radiation pollution not only negatively impacts the measurement accuracy of precision instruments, leading to distorted measurement results, but may also interfere with the normal operation of instruments and even pose a potential threat to human health. To address this problem, traditionally, solid metals and other highly conductive materials have been used as the primary means of electromagnetic interference (EMI) shielding. These materials, due to their excellent conductivity, can effectively block the propagation of electromagnetic waves (EMWs). However, the strong reflective properties of these conductive materials to EMWs can lead to secondary reflection and scattering of electromagnetic waves, thereby causing secondary electromagnetic pollution and further exacerbating the crisis in the ecosystem.

[0003] Electromagnetic waves are a wave phenomenon formed by the mutual excitation and alternating changes of electric and magnetic fields in space. Their propagation is independent of a medium and can be effectively transmitted in a vacuum and various materials. The theoretical basis of this physical phenomenon stems from Maxwell's electromagnetic field theory. According to the mathematical expression of Maxwell's equations, a time-varying electric field excites a vortex magnetic field, which in turn excites a vortex electric field. This coupled, time-varying electromagnetic field propagates in space in the form of waves, thus forming electromagnetic waves.

[0004] Electromagnetic shielding technology is a strategy that effectively blocks the propagation of electromagnetic waves by using specific materials or structural designs. It plays a crucial role in many fields, including electronic equipment, communication systems, and medical facilities, aiming to significantly reduce the negative impacts of electromagnetic interference and radiation. The underlying mechanism is complex and sophisticated, with the core being the synergistic effect of reflection, absorption, and multiple reflections. Electromagnetic shielding composite materials can be classified into reflective and absorptive types based on their shielding mechanism. Reflective electromagnetic shielding composite materials achieve their shielding function by reflecting electromagnetic waves, and their design typically considers impedance matching and the efficient reflection characteristics of electromagnetic waves. The core characteristic is that high conductivity or special structural design causes electromagnetic waves to be reflected at the material surface, thereby reducing electromagnetic wave penetration. Absorbent electromagnetic shielding composite materials achieve shielding by absorbing electromagnetic wave energy and converting it into other forms of energy (such as heat). This type of material effectively reduces electromagnetic wave reflection, thereby reducing secondary pollution, and is one of the important development directions in the current electromagnetic shielding field.

[0005] Traditional electromagnetic shielding composite materials are gradually being phased out due to their high density, complex manufacturing processes, and susceptibility to secondary pollution. Some conductive and magnetic materials (such as metals, metal oxides, carbon nanomaterials, and inherently conductive polymers) have been used for shielding and / or absorbing electromagnetic energy. Through rational structural design, conductive polymer composites (CPCs) exhibit superior performance in electromagnetic wave absorption and shielding compared to traditional electromagnetic shielding materials. In particular, porous composite membrane structures, with their abundant interfaces, can achieve better impedance matching, thus more effectively absorbing and attenuating incident electromagnetic waves. Among them, polypyrrole (PPy), a heterocyclic conjugated conductive polymer synthesized from pyrrole monomers, is widely used in electromagnetic shielding due to its excellent electrochemical properties and chemical stability. Furthermore, PPy is a polymer with strong shape plasticity, and its conductivity can vary significantly depending on the morphology and preparation method. Optimizing its electromagnetic shielding effectiveness by controlling the nanostructure is a key scientific problem urgently needing to be solved in this field. This research direction has significant theoretical and practical value for the development of high-performance electromagnetic shielding materials. Summary of the Invention

[0006] To address the aforementioned issues, this application provides a method for preparing an asymmetric electromagnetic shielding composite film. The method involves growing a MoS2 flower-like shell structure on polypyrrole nanotubes (PNTs) to obtain PNTs@MoS2 core-shell nanowires, which are then transferred to the surface of a conductive filler. A solvent-inducible phase separation technique is used to prepare an asymmetric electromagnetic shielding composite film with a three-layer structure. The conductive filler layer serves as a highly conductive layer, the PNTs@MoS2 layer is an impedance matching absorption layer, and the upper layer is a pure polylactic acid matrix layer. This significantly improves the absorption-based EMI shielding performance, thereby reducing the problem of secondary electromagnetic radiation.

[0007] To achieve the above objectives, the first technical solution of this application discloses a method for preparing an asymmetric electromagnetic shielding composite film, comprising the following steps:

[0008] S1. Preparation of PNTs@MoS2 core-shell nanowires: PNTs were dispersed in deionized water and then added to Na2MoO4·2H2O and CH4N2S. The mixture was then placed in a high-pressure reactor to react and obtain PNTs@MoS2 core-shell nanowires.

[0009] S2. The PNTs@MoS2 core-shell nanowires described in S1 are mixed and dissolved with polylactic acid and dichloromethane, and then transferred to a culture container pre-coated with conductive filler. Ethanol solution is continuously added, and the mixture is allowed to evaporate naturally at room temperature to obtain an asymmetric electromagnetic shielding composite film.

[0010] Preferably, the PNTs are prepared by placing a FeCl3·6H2O oxidant solution in a reaction system containing MO and Py monomers and reacting at a constant temperature of 4°C.

[0011] Preferably, the reaction temperature in the high-pressure reactor described in S1 is 160-220℃, and the reaction time is 20-24h.

[0012] Preferably, the mass ratio of the PNTs@MoS2 core-shell nanowires to the conductive filler in S2 is 0:1-3:2.

[0013] Preferably, the conductive filler is a ZnO&Ag composite nanomaterial, which is prepared by adding activated ZnO whiskers to a silver ammonia solution and reacting under the conditions of a reducing agent and ultrasonic stirring to obtain the ZnO&Ag composite nanomaterial.

[0014] Preferably, the method for preparing the activated ZnO whiskers is as follows: ZnO whiskers are sensitized in a mixed solution of SnCl2·2H2O, KNaC4H4O6·4H2O, and NaOH, and then activated in a mixed solution of PdCl2 and HCl.

[0015] Furthermore, the asymmetric electromagnetic shielding composite film prepared according to the above preparation method and its application as an electromagnetic shielding material in shielding electromagnetic waves.

[0016] Beneficial effects:

[0017] 1. This invention provides a method for preparing a hydrophobic electromagnetic shielding composite film with an asymmetric structure. Based on the unique physicochemical properties of MoS2, a novel three-layer composite film material was developed. A flower-like core-shell structure of MoS2 (PNTs@MoS2) was constructed on the surface of PNTs via a hydrothermal method. The layered structure and high specific surface area of ​​MoS2 enhance electromagnetic wave scattering and absorption, and dielectric loss is achieved by inducing dielectric polarization through abundant defect sites. Furthermore, combining electromagnetic shielding functionality with hydrophobic properties, a solvent-induced phase separation technique was employed (using dropwise addition of ethanol solution to induce phase separation, followed by the gradual evaporation of ethanol and dichloromethane to form a porous composite film structure). PNTs@MoS2 was introduced as an electromagnetic wave absorber into the polylactic acid / dichloromethane system, combined with an underlying silver-plated zinc oxide reflective layer, successfully preparing a PNTs@MoS2-ZnO&Ag composite film.

[0018] 2. When ZnO & Ag composite nanomaterials are used as conductive fillers, the prepared asymmetric hydrophobic electromagnetic shielding PNTs@MoS2-ZnO & Ag PLA composite film exhibits significant protrusion structures and porous network features on its surface, demonstrating excellent hydrophobic properties. An asymmetric conductive network is constructed within this unique asymmetric sandwich structure, which is highly beneficial for EMI shielding performance, which is primarily based on absorption. The asymmetric hydrophobic electromagnetic shielding PNTs@MoS2-ZnO & Ag PLA composite film offers great application potential for shielding electromagnetic interference in humid environments and demonstrates its reasonable performance. Attached Figure Description

[0019] Figure 1 These are SEM and TEM images of the PNTs@MoS2 hybrid material involved in the embodiments of the present invention: (a, b) SEM images of PNTs at different magnifications, (c, d) SEM images of PNTs@MoS2 at different magnifications, (e, f) TEM images of PNTs at different magnifications, (g, h) TEM images of PNTs@MoS2 at different magnifications, (i) EDS images of N, Mo, and S elements in PNTs@MoS2, and (j) HRTEM image of PNTs@MoS2.

[0020] Figure 2 These are SEM and XRD images of the PNTs@MoS2-ZnO&Ag PLA composite film involved in the embodiments of the present invention; wherein, (a) is a SEM image of the upper surface of the PNTs@MoS2-400ZnO&Ag PLA composite film.

[0021] (b) SEM image of the upper surface of the 200PNTs@MoS2-400ZnO&Ag PLA composite membrane.

[0022] (c) SEM image of the lower surface of the OPNTs@MoS2-400ZnO&Ag PLA composite membrane.

[0023] (d) XRD pattern of 200PNTs@MoS2-400ZnO&Ag PLA composite membrane

[0024] (e) Cross-sectional SEM image of the 0PNTs@MoS2-400ZnO&Ag PLA composite membrane.

[0025] (f) Cross-sectional SEM image of the 200PNTs@MoS2-0ZnO&Ag PLA composite membrane.

[0026] (g)200PNTs@MoS2-400ZnO&Ag PLA composite membrane cross-section SEM image.

[0027] (h) EDS plot of MO, S, and Ag elements in the cross section of the 200PNTs@MoS2-400ZnO&Ag PLA composite membrane;

[0028] Figure 3 The PNTs@MoS2-ZnO&Ag PLA composite film involved in this embodiment of the invention exhibits EMI SE in the X-band. T Average SE T SE A and SE R AR power coefficient u, where (a) EMI SET of 150PNTs@MoS2-yZnO&Ag PLA composite film in X band, (b) average SET, SEA and SER and (c) AR power coefficient; (d) EMI SET of xPNTs@MoS2-400ZnO&Ag PLA composite film in X band, (e) average SET, SEA and SER and (f) AR power coefficient;

[0029] Figure 4 The above refers to the water contact angle on the upper surface and the conductivity on the lower surface of the PNTs@MoS2-ZnO&Ag PLA composite membrane involved in the embodiments of the present invention, wherein (a) is the water contact angle on the upper surface of the PNTs@MoS2-ZnO&Ag PLA composite membrane, and (b) is the conductivity on the bottom surface of the PNTs@MoS2-ZnO&Ag PLA composite membrane. Detailed Implementation

[0030] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0031] Unless otherwise specifically stated, the relative arrangement, numerical expressions, and values ​​of the components and steps described in these embodiments do not limit the scope of this application. It should also be understood that, for ease of description, the dimensions of the various parts shown in the drawings are not drawn to actual scale. Techniques, methods, and devices known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques, methods, and devices should be considered part of the specification. In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not as limitations. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar reference numerals and letters in the following drawings denote similar items; therefore, once an item is defined in one drawing, it need not be further discussed in subsequent drawings.

[0032] Unless otherwise specified, the technical terms in this specification have the same meaning as those generally understood by those skilled in the art; however, in case of any conflict, the definitions in this specification shall prevail.

[0033] The embodiments of this application disclose a method for preparing an asymmetric electromagnetic shielding composite film, comprising the following steps:

[0034] S1. Preparation of PNTs@MoS2 core-shell nanowires: PNTs were dispersed in deionized water and then added to Na2MoO4·2H2O and CH4N2S. The mixture was then placed in a high-pressure reactor to react and obtain PNTs@MoS2 core-shell nanowires.

[0035] S2. The PNTs@MoS2 core-shell nanowires described in S1 are mixed and dissolved with polylactic acid and dichloromethane, and then transferred to a culture container pre-coated with conductive filler. Ethanol solution is continuously added, and the mixture is allowed to evaporate naturally at room temperature to obtain an asymmetric electromagnetic shielding composite film.

[0036] In this embodiment, PNTs are polypyrrole nanotubes. After adding Na2MoO4·2H2O and CH4N2S and reacting at high temperature, a flower-like shell structure of MoS2 can be grown on it. The layered structure and high specific surface area of ​​MoS2 help to enhance the scattering and absorption of electromagnetic waves, and it has abundant defect sites that can induce dielectric polarization to achieve dielectric loss.

[0037] PNTs@MoS2 core-shell nanowires were introduced as electromagnetic wave absorbers into a polylactic acid / dichloromethane system. The system was then placed in a culture vessel pre-coated with conductive filler, and ethanol solution was used as the evaporating agent for static evaporation at room temperature. By adjusting the solvent-non-solvent interaction forces, phase separation of the polylactic acid polymer chains was induced, resulting in a three-layer asymmetric electromagnetic shielding composite film consisting of conductive filler, PNTs@MoS2 structure, and polylactic acid matrix from bottom to top. This constructed an asymmetric conductive gradient network, significantly improving the absorption-based EMI shielding performance and thus reducing the problem of secondary electromagnetic radiation. In this process, ethanol induced phase separation of the polylactic acid polymer chains by adjusting the solvent-non-solvent interaction forces.

[0038] The "asymmetric electromagnetic shielding composite film" refers to a composite film with a sandwich structure, where the bottom, middle, and top layers of the composite film have different filler distributions. Different conductive components are distributed in a gradient along the thickness direction, reducing electromagnetic wave reflection and enhancing absorption loss through gradual impedance changes.

[0039] In this embodiment, the addition ratio of PNTs to Na2MoO4·2H2O and CH4N2S in S1 is 1:60-80:130-150, the reaction temperature in the high-pressure reactor is 180-200℃, and the reaction time is 22-24h.

[0040] In this embodiment, the mass ratio of the PNTs@MoS2 core-shell nanowires to the conductive filler in S2 is 0:1-3:2.

[0041] In some preferred embodiments, the PNTs are prepared by placing a FeCl3·6H2O oxidant solution in a reaction system containing MO and Py monomers and reacting at a constant temperature of 4°C. It should be noted that the reaction system should also be pre-cooled to 4°C, the preferred mass ratio of MO to Py monomers in the reaction system is 1:2-3, and the amount of FeCl3·6H2O added is 0.8g.

[0042] Figure 1 The SEM and TEM images of PNTs@MoS2 materials show that methyl orange was used as a directing agent to induce the growth of polypyrrole into hollow nanotube structures during the PNTs preparation process. The fibrous complex formed by methyl orange and the oxidant (FeCl3·6H2O) can serve as a reactive self-degrading template. During the polymerization process, pyrrole monomers undergo oxidative polymerization on the template surface, while the template itself degrades, ultimately forming hollow polypyrrole nanotubes. These images were obtained using scanning electron microscopy (SEM). Figure 1 As can be seen from (a) and (b), PNTs exhibit a nanotube morphology several micrometers long, with an outer diameter of approximately 75 nm and an inner diameter of approximately 30 nm. Figure 1 f). The surface of PNTs is relatively smooth, but under high-resolution transmission electron microscopy (TEM), some nanoscale textures and wrinkles can be seen. Figure 1 e, f). After growing MoS2 on PNTs, from the scanning electron microscope images ( Figure 1 (c, d) clearly show morphological changes, exhibiting a core-shell structure. The core is composed of polypyrrole nanotubes, and the outer shell is composed of molybdenum disulfide nanosheets, presenting an overall one-dimensional rough nanowire morphology. The molybdenum disulfide nanosheets on the outer shell exhibit a flower-like structure, epitaxially growing across the entire surface of the PNTs. The diameter of the core-shell nanowires is relatively coarser than that of the PNTs, approximately 400 to 500 nm. Furthermore, TEM images of PNTs@MoS2 ( Figure 1 (g, h) shows that MoS2 has a typical layered structure, which is a flower-like structure composed of nanosheets that diffuse outward from the center. Figure 1 The image shows the elemental distribution of PNTs@MoS2, clearly displaying the presence of N, Mo, and S elements, indicating that MoS2 was successfully deposited on the PNTs. Furthermore, Mo and S elements are uniformly distributed within the nanowires. It is also evident from the image that N elements are mainly concentrated in the core of the nanowires, while Mo and S elements are uniformly distributed in the flower-like outer shell layer. Figure 1In image j, the corresponding HR-TEM image shows that the lattice fringe spacing of MoS2 (002) is 0.7 nm. During the growth of MoS2, the structural characteristics of the polypyrrole nanotubes (PNTs) surface play a crucial role in the nucleation of MoS2 nanosheets. Specifically, defects on the PNT surface provide active sites for MoS2 nucleation. During the nucleation stage, Mo and S atoms are more easily adsorbed and aggregated at these defects, significantly reducing the nucleation energy barrier and thus promoting MoS2 growth. Furthermore, the hydrothermal reaction conditions also provide a favorable environment for the uniform growth of MoS2. Hydrothermal conditions not only promote the diffusion and atomic rearrangement of reactants but also accelerate the reaction rate, enabling Mo and S atoms to combine more efficiently and form the MoS2 structure. Notably, MoS2 itself has a layered structure, and its growth exhibits significant anisotropy. In the hydrothermal reaction, MoS2 tends to grow along the surface of PNTs, forming vertically or horizontally arranged nanosheets. The active sites on the surface of PNTs, the promoting effect of hydrothermal conditions, and the anisotropic growth characteristics of MoS2 work together to ultimately form flower-like nanowires with a core-shell structure.

[0043] In a further embodiment, the conductive filler is a highly conductive material, such as graphene, carbon fiber, carbon nanotubes, etc., preferably a ZnO&Ag composite nanomaterial, which is prepared by adding activated ZnO whiskers to a silver ammonia solution and reacting under the conditions of a reducing agent and ultrasonic stirring to obtain the ZnO&Ag composite nanomaterial; wherein the activated ZnO whiskers are prepared by sensitizing ZnO whiskers in a mixed solution of SnCl2·2H2O, KNaC4H4O6·4H2O, and NaOH, and then activating them in a mixed solution of PdCl2 and HCl.

[0044] Figure 2 The images show the SEM and XRD patterns of the PNTs@MoS2-ZnO & Ag PLA composite membrane. It can be seen that the PNTs@MoS2-ZnO & Ag PLA composite membrane with an asymmetric sandwich structure was successfully prepared using a solvent-inducible phase separation technique. The morphology and microstructure of the composite membrane were characterized and analyzed by SEM and EDS.

[0045] The upper surface of the OPNTs@MoS2-400ZnO&Ag PLA composite membrane exhibits a large number of dense microsphere structures. Figure 2a) This phenomenon can be attributed to a thermodynamically driven phase separation process that occurs when the free energy of a single-phase system is higher than that of a two-phase system. During phase separation, PLA nuclei in the polymer-rich phase form regular microsphere protrusions through the directional alignment of molecular chains along the phase interface. Notably, after introducing PNTs@MoS2 into the PLA matrix, although the morphology of the microsphere protrusions is still maintained on the upper surface, their size distribution is significantly finer than that of the PNTs@MoS2-400ZnO&Ag PLA composite film. Figure 2 b). The bottom of the composite membrane retains a complete ZnO & Ag network structure. Figure 2 c) Even during phase separation, the pre-deposited ZnO & Ag maintain their structural integrity, forming an interconnected conductive network, thus ensuring excellent conductivity at the bottom of the composite film. The cross-section of the composite film shows that the introduction of…

[0046] The porous structure inside the PNTs@MoS2 composite membrane is partially filled. Figure 2 f), compared to the composite membrane without PNTs@MoS2 ( Figure 2 e) The porosity has decreased. Figure 2 Images g and 2h show the cross-sectional morphology and elemental distribution of the 200PNTs@MoS2-400ZnO&Ag PLA composite film. SEM images clearly show that the composite film has a regular porous structure and a distinct three-layer structure: a uniformly distributed ZnO&Ag conductive layer at the bottom, a PNTs@MoS2 electromagnetic wave absorption layer in the middle, and a pure PLA porous impedance matching layer at the top. Combined with EDS elemental distribution analysis and XRD patterns (…),… Figure 2 d) The results further confirmed the successful preparation of composite membranes with asymmetric structures.

[0047] It is understood that in this embodiment, the process of obtaining pure reaction products after all reactions are completed involves steps such as centrifugation, washing, and drying, which are all conventional steps in the art.

[0048] The specific functions of the asymmetric electromagnetic shielding composite film obtained by the preparation method of this application will be described in detail below through specific embodiments.

[0049] The deionized water used in the following examples was all laboratory-prepared distilled water; the reagents involved in the preparation of PNTs@MoS2 included methyl orange (MO, AR grade), ferric chloride hexahydrate (FeCl3·6H2O, AR grade), pyrrole (Py, AR grade), sodium molybdate dihydrate (Na2MoO4·2H2O, AR grade), and thiourea (CH4N2S, AR grade); the preparation of PNTs@MoS2 was carried out using a magnetic stirrer (DF-101Z) for dispersion and stirring, and high temperature was used. The high-temperature reaction is carried out in a forced-air drying oven (XGQ-2000); the reagents involved in the preparation of ZnO & Ag include tetraneedle-shaped zinc oxide whiskers (ZnO, industrial grade), ammonia water (NH3·H2O, concentration 25-28%), silver nitrate (AgNO3, AR grade), stannous chloride (SnCl2·2H2O, AR grade), sodium hydroxide (NaOH, AR grade), formaldehyde (HCHO, concentration 37%), hydrochloric acid (HCl, 37-38wt%), and palladium chloride (PdCl2, AR grade).

[0050] The following examples all use asymmetric electromagnetic shielding composite films prepared according to the following methods:

[0051] 1. Preparation of PNTs@MoS2:

[0052] First, a 60 ml aqueous solution containing 0.082 g MO and 0.21 ml Py monomer was prepared as the reaction system, and this mixture was pre-cooled at 4 °C to ensure consistent reaction conditions. Then, under continuous stirring, 6.9 ml of freshly prepared 0.12 g / ml FeCl3·6H2O oxidant solution was slowly added dropwise to the reaction system. The entire polymerization reaction was carried out at a constant temperature of 4 °C for 24 h to ensure complete polymerization of Py monomer and formation of nanotube structures. After the reaction, the product was obtained by centrifugation and washed repeatedly with deionized water to remove unreacted monomers and byproducts. Finally, the purified PNTs were dried in a vacuum drying oven at 40 °C for 12 h to obtain the final product, PNTs.

[0053] 30 mg of PNTs were dispersed in 60 mL of deionized water, followed by the addition of 2.42 g of Na₂MoO₄·2H₂O and 4.57 g of CH₄N₂S, and stirred thoroughly for 30 min. The mixture was then transferred to a PTFE-lined high-pressure reactor and reacted at 190 °C for 24 h. After the reaction was complete, the mixture was allowed to cool naturally, and impurities were removed by washing repeatedly with deionized water. Finally, the purified PNTs@MoS₂ was freeze-dried to obtain the final product, PNTs@MoS₂.

[0054] 2. The specific preparation method for using ZnO and Ag materials as conductive fillers is as follows:

[0055] ZnO & Ag nanocomposite particles were successfully synthesized using a chemical co-deposition technique. The specific preparation process is as follows: First, a sensitization solution was prepared by dissolving 4.5 g SnCl2·2H2O, 7 g KNaC4H4O6·4H2O, and 7 g NaOH sequentially in 200 ml of dissolved glass (DIW). ZnO whiskers were then added to this solution and treated with continuous stirring and ultrasonic assistance for half an hour. After sensitization, the ZnO whiskers were thoroughly washed with the DIW and then vacuum filtered. Next, an activation solution was prepared by dissolving 10 mg PdCl2 in 100 ml of DIW and adding 0.1 ml HCl to promote dissolution. The sensitized ZnO whiskers were mixed with the activation solution and reacted with ultrasonic stirring for 30 min. The activated ZnO whiskers were washed with deionized water, filtered, and then dried in a 40℃ oven for later use. Finally, a silver ammonia solution was prepared by dissolving 500 mg AgNO3 in 100 ml DIW, adding 8 ml NH3·H2O, then adding 300 mg activated ZnO whiskers, and slowly adding HCHO reducing agent. After reacting for 30 min under ultrasonic stirring, the mixture was washed and filtered through DIW, and then vacuum dried at 40 °C to obtain ZnO&Ag composite nanomaterials.

[0056] 3. Preparation of PNTs@MoS2-ZnO&Ag PLA composite membrane:

[0057] First, a ZnO&Ag / ethanol dispersion was pre-spread in a 60 mm petri dish and allowed to evaporate at room temperature. Then, 0.9 g PLLA, 0.1 g PDLA, and PNTs@MoS2 were dissolved in 15 ml dichloromethane and stirred for 1.5 h. The mixture was then transferred to a petri dish pre-spread with ZnO&Ag, and 3 ml of ethanol solution was added dropwise. The mixture was allowed to evaporate naturally at room temperature (25 °C) for 24 h, ultimately forming a porous PNTs@MoS2-ZnO&Ag PLA composite membrane. The amounts of PNTs@MoS2 and ZnO&Ag added are shown in Table 1.

[0058] Table 1

[0059]

[0060] To provide a detailed description of the material properties and parameters in the embodiments, the following section will begin... Figures 3-4 The electromagnetic shielding performance of the materials will be further explained.

[0061] Figure 3 This refers to the electromagnetic shielding performance of the composite film when electromagnetic waves are incident through the impedance matching layer. Among these... Figure 3The 150PNTs@MoS2-yZnO&Ag PLA composite film (Examples 4, 6-9) demonstrates excellent electromagnetic shielding performance at PNTs@MoS2 addition of 150mg and ZnO&Ag addition (y = 0, 100, 200, 300, 400mg). Benefiting from its superior conductivity and unique asymmetric structural design, the PNTs@MoS2-ZnO&Ag PLA composite film exhibits outstanding electromagnetic shielding performance. Specifically, the 150PNTs@MoS2-yZnO&Ag PLA composite film without ZnO&Ag (Example 6) shows an EMI SE of less than 3dB in the X-band (8.2-12.4GHz). Figure 3 a) This is mainly due to its conductivity not meeting the requirements for conductive electromagnetic shielding materials, thus failing to form an effective electromagnetic wave reflection interface, allowing most electromagnetic waves to pass through the material. When 100mg of ZnO & Ag is pre-deposited, the EMI value of 150PNTs@MoS2-100ZnO & Ag PLA (Example 7) is significantly improved due to the excellent conductivity of ZnO & Ag, reaching 22.5dB, which is higher than the commercial standard for electromagnetic shielding materials (20dB). With increasing ZnO & Ag deposition, the electromagnetic shielding performance of the composite film shows a clear gradient improvement trend. When the ZnO & Ag pre-deposition amount reaches 400mg, the EMI shielding effectiveness of the 150PNTs@MoS2-400ZnO & Ag PLA composite film (Example 4) reaches as high as 64.2dB, demonstrating excellent electromagnetic shielding performance.

[0062] To elucidate the evolution mechanism of the electromagnetic shielding performance of PNTs@MoS2-ZnO&Ag PLA composite films, this study calculated the electromagnetic shielding performance (SE) of different ZnO&Ag deposition amounts. R SE A and SE T The electromagnetic wave absorption coefficient (A) and reflection coefficient (R) were calculated simultaneously, such as... Figure 3 As shown in b and 3c, with the increase of ZnO & Ag deposition, SE T and SE A All showed a clear upward trend, a phenomenon positively correlated with the enhanced conductivity of the ZnO & Ag layers. Figure 3 b). Overall, the SE of 150PNTs@MoS2-yZnO&Ag PLA composite films with different ZnO&Ag deposition amounts... R The changes were minimal, with a maximum of only 3 dB (150 PNTs@MoS2-400ZnO&Ag PLA, Example 4). The 150 PNTs@MoS2-400ZnO&Ag PLA composite film, however, exhibited a high SE of 64.2 dB. T SEA The value is 61.2 dB, SE R Only 3dB, SE A SE T The ratio is as high as 95.3%. The AR coefficient of the 150PNTs@MoS2-yZnO&Ag PLA composite film varies greatly under different ZnO&Ag deposition amounts. As the ZnO&Ag deposition amount gradually increases, the AR coefficient of the composite film shows a trend of first increasing and then decreasing. Among them, the 150PNTs@MoS2-100ZnO&Ag PLA composite film (Example 7) shows the highest AR coefficient (0.63), demonstrating an electromagnetic shielding mechanism mainly based on absorption.

[0063] Figure 3 df represents the xPNTs@MoS2-400ZnO&Ag PLA composite membrane: i.e., Examples 1-5, when the ZnO&Ag addition is 400mg, the electromagnetic shielding performance is measured for different PNTs@MoS2 addition amounts (x = 0, 50, 100, 150, 200mg). This study obtained the SE (electromagnetic shielding) performance under different PNTs@MoS2 addition amounts through calculation. R SE A and SE T The electromagnetic wave absorption coefficient (A) and reflection coefficient (R) were calculated simultaneously. Figure 3 d demonstrates the EMISE performance of xPNTs@MoS2-400ZnO&Ag PLA composite film in the X-band (8.2-12.4GHz). T The trend of value change. The results show that, compared with the dominant role of the ZnO&Ag conductive network, the introduction of PNTs@MoS2 has a greater impact on SE. T The improvement in SE value is relatively limited, only slightly increased. This was achieved by adjusting the SE values ​​for different amounts of PNTs@MoS2. A SE R and SE T Perform analysis ( Figure 3 e), discovered SE A The value was consistently significantly higher than SE. R The value indicates that the electromagnetic shielding mechanism of the composite film is dominated by loss absorption. Of particular note is the excellent SE value (sensitivity) of the 200PNTs@MoS2-400ZnO&Ag PLA composite film (Example 5), which is close to 65 dB. T Value, where SE A The contribution value reached 61.2 dB, while SE R Only 3.7dB, SE A / SE TThe ratio is as high as 94%. This phenomenon confirms the key role of interfacial polarization loss and multiple scattering mechanism in electromagnetic wave energy dissipation. Further analysis of the AR coefficient variation law revealed that the 100PNTs@MoS2-400ZnO&Ag PLA composite film (Example 3) exhibits the best absorption performance, with an AR value of 0.65.

[0064] Figure 4 This refers to the water contact angle of the PNTs@MoS2-ZnO&Ag PLA composite membrane and the conductivity of the lower surface. During polylactic acid (PLA) phase separation, the aggregation and solidification of the polymer phase form microscopic or nanoscale surface protrusions. The formation of these protrusions is mainly attributed to the interaction between solvent and non-solvent during phase separation and the rearrangement of polymer segments. As the solvent evaporates or the non-solvent diffuses, the polymer phase gradually solidifies, forming a surface structure with irregular morphology. These microscopic or nanoscale protrusions significantly increase the surface roughness of the membrane, thus having a significant impact on the surface properties of the material. For example... Figure 4 As shown in Figure a (Examples 1-5), the hydrophobic properties of the composite membrane were verified by water contact angle testing. After introducing PNTs@MoS2 into the polylactic acid matrix, the hydrophobicity of the upper layer of the composite membrane was not significantly affected, and its water contact angle remained above 140°. This phenomenon indicates that the addition of PNTs@MoS2 did not disrupt the porous structure and surface protrusions formed by the phase separation process, which are key factors contributing to the material's high hydrophobicity. Electrical conductivity and electromagnetic interference shielding effectiveness typically exhibit a significant positive correlation. Therefore, introducing conductive fillers into the material system is a key strategy for achieving electromagnetic shielding functionality. For example... Figure 4 As shown in Examples 4 and 6-9, the conductivity of the composite film exhibits a clear gradient increase with increasing ZnO and Ag deposition amounts. In the absence of pre-deposition...

[0065] Under ZnO & Ag layer conditions, even with a PNTs@MoS2 addition of 200 mg, the conductivity of the composite film's bottom surface is only 0.008 S / cm, far below the minimum conductivity required for effective electromagnetic shielding (typically ≥0.01 S / cm). This indicates that adding a single filler is insufficient to meet the requirements of electromagnetic shielding materials. When pre-deposited...

[0066] When the mass of ZnO and Ag increased to 400 mg, the conductivity of the composite film's bottom surface significantly improved to 38.889 S / cm. This increase indicates that the introduction of ZnO and Ag played a crucial role in the construction of the conductive network. This significant improvement in conductivity is mainly attributed to the penetration threshold effect between ZnO and Ag particles. That is, when the concentration of the conductive filler reaches a certain critical value, a continuous three-dimensional conductive network forms between the particles, thereby significantly improving the material's conductivity. Furthermore, the high conductivity and good dispersibility of ZnO and Ag particles further promote the formation of conductive pathways and optimize the transport path of charge carriers. The construction of this conductive network significantly enhances the conductivity of the composite film and also improves the material's attenuation capability for electromagnetic waves through multiple reflection and absorption mechanisms, thus endowing the material with excellent electromagnetic shielding performance.

[0067] This invention employs a controllable synthesis strategy. First, polypyrrole nanotubes (PPNs) are prepared as precursors. Then, molybdenum disulfide is grown in situ on their surface using a hydrothermal method, successfully constructing a PNTs@MoS2 hybrid material with a flower-like core-shell structure. Based on this, we use a one-step phase separation method to prepare an asymmetric electromagnetic shield with hydrophobic properties.

[0068] PNTs@MoS2-ZnO&Ag PLA composite membrane. To systematically evaluate the comprehensive performance of this composite material, its microstructure and electromagnetic shielding performance were characterized and analyzed from multiple dimensions. The results show that:

[0069] (1) By constructing an asymmetric structure, a gradient distribution of material conductivity was achieved: a highly conductive ZnO&Ag layer was used as a reflective layer, PNTs@MoS2 as an impedance matching absorption layer, and a pure PLA substrate layer was placed on top, forming an optimized conductivity gradient network. This structural design significantly improved the EMI shielding performance of the material, which is mainly absorption-based. Among them, the 150PNTs@MoS2-400ZnO&Ag PLA composite film exhibited excellent electromagnetic shielding effectiveness (64.2dB) at a thickness of 1mm, far exceeding the commercial standard (20dB), and its absorption coefficient reached 0.65, confirming its efficient electromagnetic wave absorption capability.

[0070] (2) The material surface exhibits excellent hydrophobic properties, with a water contact angle reaching up to 147.2°. Notably, after introducing PNTs@MoS2 into the PLA matrix, the upper layer of the composite film still maintains good hydrophobicity, with the water contact angle remaining stable above 140°. This unique structural design not only ensures the electromagnetic shielding performance of the material under normal conditions, but more importantly, it significantly improves its long-term stability in humid or polluted environments, providing a reliable guarantee for practical applications.

[0071] In summary, this invention discloses a method and application for preparing an asymmetric electromagnetic shielding composite film using core-shell PNTs@MoS2 nanowires combined with phase separation. The preparation method involves: firstly, preparing polypyrrole nanotubes (PNTs), and then growing a flower-like shell structure of MoS2 on the PNTs. The layered structure and high specific surface area of ​​MoS2 help enhance the scattering and absorption of electromagnetic waves, and its abundant defect sites can induce dielectric polarization to achieve dielectric loss. Subsequently, a layer of silver-plated zinc oxide is pre-layered at the bottom of a culture dish. Molybdenum disulfide hybridized polypyrrole nanotubes (PNTs@MoS2) are added to a polylactic acid / dichloromethane solution as an ideal electromagnetic wave absorber. A three-layered PNTs@MoS2-ZnO&Ag PLA composite film is successfully prepared using a solvent-inducing phase separation technique.

[0072] The 150PNTs@MoS2-400ZnO&Ag PLA composite film exhibited excellent electromagnetic shielding performance (64.2dB) and an absorption coefficient of 0.65, demonstrating its highly efficient electromagnetic wave absorption capability.

[0073] Therefore, those skilled in the art will recognize that although embodiments of the present invention have been shown and described in detail herein, many other variations or modifications conforming to the principles of the present invention can be directly determined or derived from the disclosure of the present invention without departing from the spirit and scope of the invention. Therefore, the scope of the present invention should be understood and recognized as covering all such other variations or modifications.

Claims

1. A method for preparing an asymmetric electromagnetic shielding composite film, characterized in that, Includes the following steps: S1. Preparation of PNTs@MoS2 core-shell nanowires: PNTs were dispersed in deionized water and then added to Na2MoO4·2H2O and CH4N2S. The mixture was then placed in a high-pressure reactor to react and obtain PNTs@MoS2 core-shell nanowires. S2. The PNTs@MoS2 core-shell nanowires described in S1 are mixed and dissolved with polylactic acid and dichloromethane, and then transferred to a culture container pre-coated with conductive filler. Ethanol solution is continuously added, and the mixture is allowed to evaporate naturally at room temperature to obtain an asymmetric electromagnetic shielding composite film.

2. The preparation method according to claim 1, characterized in that, The PNTs are prepared by placing a FeCl3·6H2O oxidant solution in a reaction system containing MO and Py monomers and reacting at a constant temperature of 4℃.

3. The preparation method according to claim 1, characterized in that, The reaction temperature in the high-pressure reactor described in S1 is 160-220℃, and the reaction time is 20-24h.

4. The preparation method according to claim 1, characterized in that, The mass ratio of the PNTs@MoS2 core-shell nanowires to the conductive filler in S2 is 0:1-3:

2.

5. The preparation method according to claim 1, characterized in that, The conductive filler is a ZnO&Ag composite nanomaterial, which is prepared by adding activated ZnO whiskers to a silver ammonia solution and reacting under the conditions of a reducing agent and ultrasonic stirring to obtain the ZnO&Ag composite nanomaterial.

6. The preparation method according to claim 1, characterized in that, The method for preparing the activated ZnO whiskers is as follows: ZnO whiskers are sensitized in a mixed solution of SnCl2·2H2O, KNaC4H4O6·4H2O, and NaOH, and then activated in a mixed solution of PdCl2 and HCl.

7. An asymmetric electromagnetic shielding composite film obtained by the preparation method according to any one of claims 1-6.

8. The application of the asymmetric electromagnetic shielding composite film according to claim 7 as an electromagnetic shielding material in shielding electromagnetic waves.

Citation Information

Cited By

  • Preparation method and application of composite membrane based on CNTs (at) Co (at) MoS2 heterostructure

    CN121848806A